2018
DOI: 10.1016/j.joca.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the future burden of opioids for osteoarthritis

Abstract: OA-related opioid dispensing and associated costs are set to increase substantially in Australia from 2015/16 to 2030/31. Use of opioids for OA pain is concerning given joint disease chronicity and the risk of adverse events, particularly among older people. These projections represent a conservative estimate of the full financial burden given additional costs associated with opioid-related harms and out-of-pocket costs borne by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
(35 reference statements)
5
30
1
Order By: Relevance
“…However, oxycodone is increasingly being prescribed for patients with OA according to the present study. This is in agreement with other studies, which also found increases in the prescription rate of oxycodone for OA [ 12 ] and strong opioids for musculoskeletal pain in general [ 21 ]. At the same time as the prescription rates for oxycodone and fentanyl increased, the prescription rates for paracetamol/codeine and tramadol/paracetamol decreased.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, oxycodone is increasingly being prescribed for patients with OA according to the present study. This is in agreement with other studies, which also found increases in the prescription rate of oxycodone for OA [ 12 ] and strong opioids for musculoskeletal pain in general [ 21 ]. At the same time as the prescription rates for oxycodone and fentanyl increased, the prescription rates for paracetamol/codeine and tramadol/paracetamol decreased.…”
Section: Discussionsupporting
confidence: 93%
“…Most of the studies examining opioid prescriptions in OA patients found an increase in the prescription rate [ 12–14 , 19 ] while we found a relatively stable prescription rate. One study looking at US insurance data claims also found a relatively stable opioid prescription rate [ 20 ].…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…The development of effective therapeutics for optimal pain management has lagged behind other areas, such as inflammation control and the regulation of autoimmunity, which is partially responsible for the current epidemic of opioid and narcotic abuse. A recent report showed that nearly 10% of all opioids prescribed in Australian general practice are prescribed for OA [4]. Similarly, in a survey of Swedish residents aged ≥35 years, 12% of incident opioid dispensations were attributable to OA and/or its related comorbidities [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is inconclusive evidence for the benefits of opioids for arthritides and increasing awareness of the risks, opioid prescription rates for OA in the USA remained stable between 2007 and 2014 [6]. On the other hand, despite recent advances in the treatment of RA utilizing effective immunosuppressive therapies based on a better understanding of its underlying mechanism, remaining pain affected almost one third of early RA patients with a good clinical response [4]. By 2014, 41% of patients with RA in the USA were regular users of opioids [7].…”
Section: Introductionmentioning
confidence: 99%